v.4 - Roy, M. N.; Ray,Sibnarayan (ed.) (Delhi, 1997)
This fourth volume of M. N. Roy's Selected Works (1932-6) comprises his prison writings, which range from politics to philosophy. from history to sociology of religion and culture, and which show the beginnings of his transformation from a communist to a radical humanist.
Keywords: Marxism